Global patterns of ranavirus detections - Jesse L. Brunner; Deanna H. Olson; Matthew J. Gray; Debra L. Miller; Amanda L.J. Duffus (Canadian Science Publishing, 2021)
Ranaviruses are emerging pathogens of poikilothermic vertebrates. In 2015 the Global Ranavirus Reporting System (GRRS) was established as a centralized, open access, online database for reports of the presence (and absence) of ranavirus around the globe. The GRRS has multiple data layers (e.g., location, date, host(s) species, and methods of detection) of use to those studying the epidemiology, ecology, and evolution of this group of viruses. Here we summarize the temporal, spatial, diagnostic, and host-taxonomic patterns of ranavirus reports in the GRRS. The number, distribution, and host diversity of ranavirus reports have increased dramatically since the mid 1990s, presumably in response to increased interest in ranaviruses and the conservation of their hosts, and also the availability of molecular diagnostics. Yet there are clear geographic and taxonomic biases among the reports. We encourage ranavirus researchers to add their studies to the portal because such collation can provide collaborative opportunities and unique insights to our developing knowledge of this pathogen and the emerging infectious disease that it causes.